Influence of Training Exercise on Clinical Plasma Chemistry Parameters and Cardiac Markers in Race Horses - Choosri Sribhen; Anuchit Sitthichaiyakul; Yuwadee Kongpiromchean; Kosit Sribhen (Agriculture and Natural Resources, 2007)
Physiological variations of clinical chemistry parameters as a function of exercise reflecting general health and performance are largely unknown in race horses. To assess changes in blood biochemical variables, with special emphasis on cardiac markers, blood samples were drawn from twelve healthy race horses (6 males and 6 females; age range from 2 to 6 years) before and after the exercise training. Biochemical parameters in the renal, liver and lipid profile as well as the muscle enzymes creatine kinase (CK), aspartate aminotransferase (AST) and lactate dehydrogenase (LDH) were measured with standard methods using an automated analyzer Hitachi 917 (Roche Diagnostics). Cardiac troponin I (cTnI) plasma concentrations were analyzed with immunometric luminescence technology utilizing an automated immunoassay analyzer Vitros ECi (Ortho-Clinical Dianostic). With the exception of triglycerides, all other biochemical variables showed increased levels after the exercise, with values for alanine aminotransferase (ALT), albumin and total protein reaching statistical significance. The activities of CK and LDH, but not of AST, also displayed a significant increase after the training. Comparing with pre-exercise mean value of 0.015 ng/ml, a more than 10 fold increase in cTnI concentration (0.177 ng/ml) was observed, with a maximum value as high as 0.498 ng/ml. The majority of animals (58%) showed levels exceeding lower cut-off concentration of cTnI at 0.12 ng/ml indicative of a small myocyte injury. In conclusion, small changes in levels of the routine blood chemistry parameters due to training exercise are common in race horses. There was biochemical evidence of minor myocardial cell damage as assessed by cardiac troponin I plasma concentrations.